THE INFLUENCE OF WORK COMPETENCE, WORKLOAD AND JOB SATISFACTION ON THE WORK PRODUCTIVITY OF EMPLOYEES OF PT. SCHLEMMER AUTOMOTIVE INDONESIA PART FINAL INSPECTION - Yuan Badrianto; Indah Kusumawati; Winda Widia (ZILLZELL MEDIA PRIMA, 2023)
A company is said to be successful in developing if it is able to maximize the company's productivity of its human resources. One of the efforts to increase employee work productivity is by looking at variousskills and knowledge possessed, workload and job satisfaction in employees. This study aims to find out how much influence Work Competence has on Productivity, Workload on Productivity and Job Satisfaction on Productivity. This research was conducted at PT. Schlemmer Automotive Indonesia. This type of research is quantitative. The sampling method in this study is nonpropability sampling orsaturated sample. The sample taken in this study was 65 respondents. This research method uses amultiple regression analysis method because the number of variables in this study is more than two variables. The variables used are Competence (X1), Workload (X2) and Job Satisfaction (X3) asindependent variables and Work Productivity (Y) as dependent variables. The results of the test on the ftest obtained f count 9.285 > f table 2.75 with the sig value. by 0.000 < 0.05. the t test obtained t count work competence (X1) of 2.651 > t table 1.999 with a sig value. 0.010 < 0.05, Workload (X2) of 2.225 > t table 1.999 with a sig value of 0.030 < 0.05 and Job Satisfaction (X3) of 2.644 > t table 1.999 withsig. 0.010<0.05 and the coefficient of determination test was obtained adjusted R Square value of 0.280. The results of this study resulted in that Work Competence (X1), Workload (X2) and JobSatisfaction (X3) were partially accepted and simultaneously had a positive and significant effect on employee work productivity at PT. Schlemmer Automotive Indonesia.